Need for Speed: Is Faster Trade in the EU Trade-Creating? - Cecília Hornok (The Vienna Institute for International Economic Studies (wiiw), 2011)
Timeliness has gained growing importance in international trade. This paper provides empirical evidence on the significant cost of time in trade by exploiting the quasi-experimental nature of the European Union (EU) enlargement in 2004. It applies a difference-in-difference-in-differences econometric strategy on a European industry-level database of bilateral trade barriers, where industries are differentiated according to their time sensitivity. The use of a treatment intensity indicator that captures the decline in the waiting time at borders supports the identification. Results are cross-checked on subsamples defined along transport mode choice probabilities, where intra-EU transport mode choice projections are obtained from an estimated discrete choice model on extra-EU trade. Robustness checks experiment with alternative definitions of treatment sensitivity and treatment intensity.
Keywords: F13; F14; F15; 330; time cost of trade; difference-in-difference-in-differences estimation; treatment intensity; EU enlargement; transport mode choice